2019
DOI: 10.3390/su11184911
|View full text |Cite
|
Sign up to set email alerts
|

Energy Sustainability Analysis (ESA) of Energy-Producing Processes: A Case Study on Distributed H2 Production

Abstract: In the sustainability context, the performance of energy-producing technologies, using different energy sources, needs to be scored and compared. The selective criterion of a higher level of useful energy to feed an ever-increasing demand of energy to satisfy a wide range of endo- and exosomatic human needs seems adequate. In fact, surplus energy is able to cover energy services only after compensating for the energy expenses incurred to build and to run the technology itself. This paper proposes an energy sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 56 publications
(64 reference statements)
0
18
1
Order By: Relevance
“…The study showed an energy index equal to 4.19 and 4.31 per kilogram of diesel and gasoline, respectively. In this context, the research findings highlight that, since 2011, there has been a tendency to consider, apart from EROEI or EROI, some sustainable indices such as carbon footprint (CF) (Zupko 2019;Manouchehrinejad et al 2020;Roles et al 2020), energy payback time (EPBT) (Perez et al 2011;Bhandari et al 2015;Koppelaar 2017;Pickard 2017;Walmsley et al 2018;Gómez-Camacho and Ruggeri 2019;Goel et al 2020), energy return on carbon invested (EROC) (Liu and Van den Bergh 2020), energy sustainability analysis (ESA) (Gómez-Camacho and Ruggeri 2019) or carbon-equivalent payback time (CPBT) (Perez et al 2011). In fact, 26 documents consider these indices connected with EROEI values, indicating an increasing interest towards both energy efficiency and sustainable aspects of RES.…”
Section: Biomassmentioning
confidence: 99%
“…The study showed an energy index equal to 4.19 and 4.31 per kilogram of diesel and gasoline, respectively. In this context, the research findings highlight that, since 2011, there has been a tendency to consider, apart from EROEI or EROI, some sustainable indices such as carbon footprint (CF) (Zupko 2019;Manouchehrinejad et al 2020;Roles et al 2020), energy payback time (EPBT) (Perez et al 2011;Bhandari et al 2015;Koppelaar 2017;Pickard 2017;Walmsley et al 2018;Gómez-Camacho and Ruggeri 2019;Goel et al 2020), energy return on carbon invested (EROC) (Liu and Van den Bergh 2020), energy sustainability analysis (ESA) (Gómez-Camacho and Ruggeri 2019) or carbon-equivalent payback time (CPBT) (Perez et al 2011). In fact, 26 documents consider these indices connected with EROEI values, indicating an increasing interest towards both energy efficiency and sustainable aspects of RES.…”
Section: Biomassmentioning
confidence: 99%
“…Different sustainability studies must go beyond economic analysis due to the intrinsic and complex nature of economic markets. For example, a photovoltaic system installed in Europe, but produced abroad, has an energy burden for society in terms of energy [54][55][56].…”
Section: Energy and The Dimensions Of Sustainabilitymentioning
confidence: 99%
“…Alternatively, the liquid effluent of carboxylic acids and solvents from the DF process can be fed into different processes (see Fig. 1), thus increasing value addition and improving the sustainability of the process [8,9]. This can be achieved by additional energy production as it occurs in microbial fuel cells (MFCs) [10], algae and microalgae cultivations [11], and other multi-cascade reactor configurations [7], as well as in the synthesis of valuable chemicals [12].…”
Section: Introductionmentioning
confidence: 99%
“…Enzymatic systems suffer from sensitivity to O 2 [8,14] and H 2 , which reduces the efficiency of these systems, although novel approaches are actively being researched to overcome this drawback [15]. Pure fermentative cultures (natural or engineered strains) require high sterilization costs that are currently unsustainable [9] and can lead to a negative net energy balance [8]. Open mixed fermentative cultures, such as those used in DF, are preferred due to their high production rates and their simplicity of operation [15].…”
Section: Introductionmentioning
confidence: 99%